Pengembangan Sistem Informasi Peminjaman Fasilitas Kampus Berbasis Natural Language Processing dengan Metode Extreme Programming - Maulana, Mohammad Reza; Kamal, Muhammad Rikzam; Nugroho, Agus Susilo; Tamamudin (LogicLink, 2025)
The facility (room and equipment) loan system within the Fakultas Ekonomi dan Bisnis (FEBI), Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan is still carried out manually, often using online forms and direct communication with staff. This manual process causes various problems, including schedule conflicts, asynchronous data, and a lack of transparency regarding space and asset availability. This study aims to develop a Natural Language Processing (NLP)-based Room and Equipment Loan Information System that is integrated, transparent, and can work in real-time. The system development method used is Extreme Programming (XP), which was chosen because of its adaptive, flexible nature, and focus on rapid iteration and continuous feedback from users. The XP stages include planning, design, coding, and testing. The information system is designed using the Laravel framework supported by a PostgreSQL database. The system's main functionality includes online loan applications by Borrowers, automatic validation of schedule conflicts, and approval by the Admin/Superadmin. The results show that this system is able to simplify processes, minimize schedule conflicts, and increase efficiency and transparency in the management of faculty assets.